Canadian university research libraries during the early days of the COVID-19 pandemic - Intahchomphoo, Channarong; Brown, Michelle (The Canadian Journal of Information and Library Science / La Revue canadienne des sciences de l’information et de bibliothéconomie)

(untitled) (Canadian Association for Information Science - Association canadienne des sciences de l'information, 2021)
This paper documents the services and changes that library staff at a group of 15 Canadian university research libraries highlighted on their main pandemic pages and social media accounts during the early days of the coronavirus (COVID-19) pandemic. Findings suggest that libraries in the samples adopted the following services and changes: closing the physical libraries; suspending all physical collection services and in-person events; continuing to provide virtual reference services; promoting access and usage of electronic collections; suspending late fees and renewing checked-out items with a new due date; and advising users to wait before returning borrowed items. Notably, all libraries in this study are operating as full full-scale as digital libraries. This study will provide lessons learned to other libraries around the world to help in reviewing their own operational policies for coping with the current COVID-19 pandemic and for future global public health crises.